2017
DOI: 10.1155/2017/7697345
|View full text |Cite
|
Sign up to set email alerts
|

Transfer and Metabolism of Triadimefon Residues from Rape Flowers to Apicultural Products

Abstract: This paper presents a study on the transfer and metabolism of triadimefon residues from rape flowers to apicultural products. In the field trials, honeybee colonies were placed in four rape greenhouses treated with triadimefon on standard dosage. Apicultural products (pollen, honey, and royal jelly) were collected on a regular basis. Sample preparation and extraction procedure were established. HPLC/ESI-MS/MS method was validated. The respective residues of triadimefon and metabolite triadimenol were 0.03 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Thus, the major presence of carbendazim with a 99.0% incidence in this study was not surprising. In combination with previously published data, our study also found that carbendazim was commonly present in various honeybee products in different countries (Amulen et al., 2017; David et al., 2016; Li et al., 2017). At field levels, Carbendazim was not an acutely lethal pesticide; however, field‐realistic concentrations of carbendazim (45.1 µg/kg) might harm P450‐mediated detoxification and the immune system of honeybees (Cang et al., 2012; Shi et al., 2018).…”
Section: Resultssupporting
confidence: 89%
“…Thus, the major presence of carbendazim with a 99.0% incidence in this study was not surprising. In combination with previously published data, our study also found that carbendazim was commonly present in various honeybee products in different countries (Amulen et al., 2017; David et al., 2016; Li et al., 2017). At field levels, Carbendazim was not an acutely lethal pesticide; however, field‐realistic concentrations of carbendazim (45.1 µg/kg) might harm P450‐mediated detoxification and the immune system of honeybees (Cang et al., 2012; Shi et al., 2018).…”
Section: Resultssupporting
confidence: 89%
“…Extraction and purification procedures followed the buffered QuEChERS (Quick, Easy, Cheap, Effective, Rugged and Safe) method . The procedures were almost the same as those used in our earlier studies . A representative 6 g portion of thoroughly homogenized rapeseed sample was weighed in a 50 mL centrifuge tube, followed by the addition of 9 mL of purified water and 15 mL acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28] The procedures were almost the same as those used in our earlier studies. 12 A representative 6 g portion of thoroughly homogenized rapeseed sample was weighed in a 50 mL centrifuge tube, followed by the addition of 9 mL of purified water and 15 mL acetonitrile. Then the tube was shaken vigorously for 1 min using a vortex mixer.…”
Section: Extraction and Purification Proceduresmentioning
confidence: 99%
See 2 more Smart Citations